Fine Depiction of the Single Sand Body and Connectivity Unit of a Deltaic Front Underwater Distributary Channel: Taking the Third Member of the Dongying Formation in the Cha71 Fault Block of the Chaheji Oilfield as an Example - Zhenfeng Yu; Jindong Yang; Xinya Song; Jin Qiao (Geofluids)
By taking the third member of the Dongying Formation in the Cha71 fault block of the Chaheji oilfield as an example, the single sand body of the deltaic front underwater distributary channel is meticulously depicted by using the data of well logging and performance production. Portrays the vertical separation model, total lateral separation type, vertical type, lateral superposition type, 4 types of single sand body vertical superimposed and bay type, bank contact between docking, instead of four kinds of single sand body lateral contact type, and summarizes its logging facies identification. The quantitative prediction model of the single sand body was established, the characteristics of single sand body plane distribution were summarized, and the identification of the oil-water layer and the lower limit of reservoir effective thickness were studied. And we got the conclusion that based on the fine characterization of the single sand body and the lower limit standard of effective reservoir thickness, the distribution range of the effective reservoir and connecting unit is determined. Finally, the connectivity of the connecting unit is verified by dynamic data.